Cognitive behavioural group therapy for low self-esteem : an outcome study - Gunnhildur Ólafsdóttir 1984- (2017)
Background: Self-esteem is considered to be a significant influential factor concerning well-being. Low self-esteem (LSE) is known to be associated with various mental disorders as an etiological- or maintaining factor and as a consequence. Cognitive Behavioural Therapy (CBT) has been found to be effective in improving LSE. Aims: The study aim was to evaluate the effectiveness of a group CBT designed to treat LSE. Method: Data from 104 adult participants attending a four-week (8 sessions) group CBT for LSE from 2014 to 2017 at Reykjalundur Rehabilitation Center in Iceland were evaluated. Participants completed pre- and post- treatment questionnaires on the level of self-esteem, quality of life, depression, anxiety and stress. Results: Pre-post differences were statistically significant on all measurements. Self-esteem improved, quality of life increased and depression, anxiety and stress decreased. Effect sizes were large on the measurements of self-esteem (d = 0.92), quality of life (d = 0.80) and moderate for depression, anxiety and stress (d = 0.59 – 0.62). On the primary outcome measures of self-esteem, 42% of the participants either indicated a clinically significant change or a reliable improvement. On the secondary outcome measures, these figures were 49% for quality of life, 53% for depression, 43% for anxiety and 52% for stress. Conclusions: These results entail that group CBT for LSE is potentially an effective treatment for low self-esteem and may have additional effects leading to improvement in quality of life and associated psychological problems such as depression, anxiety and stress. Keywords: Cognitive behavioural therapy, self-esteem, quality of life, depression, anxiety, stress, rehabilitation